Features of the development of the theory of balancing between benefits and harms in administrative law - S. Younis, Thanon (Academic Journal of Nawroz University, 2021)
The theory of balancing between benefits and harms under the auspices of the French Council of State in 1971, specifically on the issue of the "Eastern City" issue. The beginnings of this theory in the Egyptian State Council date back to 1961, but it became clear in the case of "Izbat Khairallah" in 1991, and then the case of "Rawd al-Farag market" and "Qursaya Island". To sum up, both of the two courts - the Egyptian and French State Council - have taken the budget theory criterion - whether the criterion of private property right, the criterion of the financial cost of the project, or the criterion of the social effects resulting from the project - and the difference between them is that the French State Council has declared its adoption of these standards, While the Egyptian State Council, as usual, adhered to traditional frameworks and implicitly declared that it worked with this theory. This theory became famous in the circles of jurisprudence and administration, and it is natural that the theory met with wide acceptance and rejection at the same time, and the second half of the last century was the most brilliant image of this theory - the era of progress and advancement of civilization and urbanism - at the time. And the truth - in my opinion, is that some have exaggerated in describing the future of this theory at the time, and it is noticed by us that the star of this theory has gradually begun to fade, in our day, although this does not diminish the importance of this theory at a stage when countries were in dire need of the budget theory Between the benefits and harms in the matter of expropriation for the public benefit.